Managerial Share Ownership and the Stock Price Effects of Antitakeover Amendment Proposals. - Mcwilliams, Victoria B (Journal of Finance, 1990)
Studies that test for an average stock price effect of antitakeover amendments present different results, disagreeing with respect to both the significance and the direction of the effect. This study determines whether effects can be identified when managerial share ownership and amendment type are considered. Results suggest a negative relation between managerial share ownership and the stock price reaction to all but fair price amendment proposals.